Clinical Utility of 18F-PSMA-1007 Positron Emission Tomography/Magnetic Resonance Imaging in Prostate Cancer: A Single-Center Experience - Liu, Ao; Zhang, Miao; Huang, Hai; Zhang, Chuanjie; Ruan, Xiaohao; Lin, Wenhao; Li, Biao; Chen, Lu; Xu, Danfeng (Frontiers in Oncology, 2021)
Purpose: We aimed to evaluate the clinical utility of 18F-PSMA-1007 positron emission tomography (PSMA PET)/magnetic resonance imaging (MRI) imaging in patients with suspected or defined prostate cancer. Methods: In the pilot study, we retrospectively investigated 62 patients who underwent PSMA-PET/MRI for suspected or defined PCa between June 2019 and June 2020. Patients were grouped into three subgroups: (1) suspected PCa without histological evidence, (2) primary PCa, (3) biochemical recurrent prostate cancer (BRPCa). Management strategies before PSMA-PET/MRI were retrospectively reported, and the management strategy was re-evaluated for each patient considering the PSMA-PET/MRI result. The changes in strategies were recorded. Besides, the correlation between prostate specific antigen (PSA) level and management changes was also accessed, and two-side p<0.05 was assumed as statistical significance. Results: There were 28 patients in the suspected PCa group (group 1), 12 in the primary PCa group (group 2), and 22 in the BRPCa group (group 3). Overall, the intended decisions were changed in 26 (41.9%) of 62 patients after PSMA-PET/MRI, including 11/28 (39.3%) in suspected PCa group, 1/12 (8.4%) in primary PCa group, and 14/24 (63.6%) in BCR group. In group 1, the main impact on subsequent management included decreased active surveillance (from 20 to 9) and increased prostate biopsy (from 8 to 19). PSA levels were not significantly associated with management changes in suspected PCa patients (p=0.865). In group 2, the main impact on subsequent management included decreased radical surgery (from 8 to 7), and multimodal therapy appearance (n=1). Only in the category of PSA levels of ≥20ng/ml, the management of primary PCa was changed. In group 3, the main impact on subsequent management included decreased salvage radiotherapy (from 5 to 2), increased systemic therapy (from 6 to 7) and increased multimodal therapy (from 11 to 13). The highest proportion of management changes occurred in BCR patients with 0.5≤PSA<1 ng/ml. Conclusion: From our preliminary experience, PSMA-PET/MRI may be a valued tool for defining PCa lesions and changing management. The biggest impact of management intent was in patients with BRPCa, especially in patients with 0.5≤PSA<1 ng/ml. Further studies are needed to confirm our pilot findings.